Cancer Metabolism: The Role of Immune Cells Epigenetic Alteration in Tumorigenesis, Progression, and Metastasis of Glioma - Kanwore, Kouminin; Kanwore, Konimpo; Adzika, Gabriel Komla; Abiola, Ayanlaja Abdulrahman; Guo, Xiaoxiao; Kambey, Piniel Alphayo; Xia, Ying; Gao, Dianshuai (Frontiers in Immunology, 2022)
Glioma is a type of brain and spinal cord tumor that begins in glial cells that support the nervous system neurons functions. Age, radiation exposure, and family background of glioma constitute are risk factors of glioma initiation. Gliomas are categorized on a scale of four grades according to their growth rate. Grades one and two grow slowly, while grades three and four grow faster. Glioblastoma is a grade four gliomas and the deadliest due to its aggressive nature (accelerated proliferation, invasion, and migration). As such, multiple therapeutic approaches are required to improve treatment outcomes. Recently, studies have implicated the significant roles of immune cells in tumorigenesis and the progression of glioma. The energy demands of gliomas alter their microenvironment quality, thereby inducing heterogeneity and plasticity change of stromal and immune cells via the PI3K/AKT/mTOR pathway, which ultimately results in epigenetic modifications that facilitates tumor growth. PI3K is utilized by many intracellular signaling pathways ensuring the proper functioning of the cell. The activation of PI3K/AKT/mTOR regulates the plasma membrane activities, contributing to the phosphorylation reaction necessary for transcription factors activities and oncogenes hyperactivation. The pleiotropic nature of PI3K/AKT/mTOR makes its activity unpredictable during altered cellular functions. Modification of cancer cell microenvironment affects many cell types, including immune cells that are the frontline cells involved in inflammatory cascades caused by cancer cells via high cytokines synthesis. Typically, the evasion of immunosurveillance by gliomas and their resistance to treatment has been attributed to epigenetic reprogramming of immune cells in the tumor microenvironment, which results from cancer metabolism. Hence, it is speculative that impeding cancer metabolism and/or circumventing the epigenetic alteration of immune cell functions in the tumor microenvironment might enhance treatment outcomes. Herein, from an oncological and immunological perspective, this review discusses the underlying pathomechanism of cell-cell interactions enhancing glioma initiation and metabolism activation and tumor microenvironment changes that affect epigenetic modifications in immune cells. Finally, prospects for therapeutic intervention were highlighted.